Spatial entanglement in interacting Bose-Einstein condensates - Sánchez-Kuntz, Natalia; Flörchinger, Stefan (Physical review, 2021)
The entanglement between spatial regions in an interacting Bose-Einstein condensate is investigated using a quantum field theoretic formalism. Regions that are small compared to the healing length are governed by a nonrelativistic quantum field theory in the vacuum limit, and we show that the latter has vanishing entanglement. In the opposite limit of a region that is large compared to the healing length, the entanglement entropy is like in the vacuum of a relativistic theory where the velocity of light is replaced with the velocity of sound and where the inverse healing length provides a natural ultraviolet regularization scale. Besides the von Neumann entanglement entropy, we also calculate Rényi entanglement entropies for a one-dimensional quasicondensate.